A phase I/IIa safety and efficacy trial of intratympanic gamma-secretase inhibitor as a regenerative drug treatment for sensorineural hearing loss - Schilder, Anne G. M.; Wolpert, Stephan; Saeed, Shakeel; Middelink, Leonie M.; Edge, Albert S. B.; Blackshaw, Helen; Pastiadis, Kostas; Bibas, Athanasios G. (Nature communications, 2024)
Inhibition of Notch signalling with a gamma-secretase inhibitor (GSI) induces mammalian hair cell regeneration and partial hearing restoration. In this proof-of-concept Phase I/IIa multiple-ascending dose open-label trial (ISRCTN59733689), adults with mild-moderate sensorineural hearing loss received 3 intratympanic injections of GSI LY3056480, in 1 ear over 2 weeks. Phase I primary outcome was safety and tolerability. Phase lla primary outcome was change from baseline to 12 weeks in average pure-tone air conduction threshold across 2,4,8 kHz. Secondary outcomes included this outcome at 6 weeks and change from baseline to 6 and 12 weeks in pure-tone thresholds at individual frequencies, speech reception thresholds (SRTs), Distortion Product Otoacoustic Emissions (DPOAE) amplitudes, Signal to Noise Ratios (SNRs) and distribution of categories normal, present-abnormal, absent and Hearing Handicap Inventory for Adults/Elderly (HHIA/E). In Phase I ( N = 15, 1 site) there were no severe nor serious adverse events. In Phase IIa ( N = 44, 3 sites) the average pure-tone threshold across 2,4,8 kHz did not change from baseline to 6 and 12 weeks (estimated change −0.87 dB; 95% CI −2.37 to 0.63; P = 0.252 and −0.46 dB; 95% CI −1.94 to 1.03; P = 0.545, respectively), nor did the means of secondary measures. DPOAE amplitudes, SNRs and distribution of categories did not change from baseline to 6 and 12 weeks, nor did SRTs and HHIA/E scores. Intratympanic delivery of LY3056480 is safe and well-tolerated; the trial’s primary endpoint was not met. Pharmacological inhibition of gamma-secretase induced partial recovery of hearing in animal models. Here, the authors present the safety and efficacy results and key learnings of the First in Human Phase I/IIa study of a gamma-secretase inhibitor in patients with acquired Hearing Loss.